Implementación de manual de buenas prácticas de manufactura para mejorar la inocuidad del almidón en la empresa “Yuca Pan” - Alvarado Lucas, María Victoria (2022)
The objective of this research was the implementation of Good Manufacturing Practices manuals in the microenterprise "Yuca Pan" in order to comply with starch indicators as required by FAO. The methods applied were laboratory and descriptive, where a diagnosis was made by means of a checklist that allowed to know the initial and final compliance with the GMP, as well as physicochemical and microbiological analysis of the starch, in order to determine the safety of the product. The current state of compliance before the implementation of the research was evidenced; the company had 36% compliance, and the physicochemical (moisture >13%, ash >0.12, pH <4.55 and starch content <92%) and microbiological (total coliforms >10 CFU/g) variables were outside the range established by the FAO. During implementation, the company collaborated in the preparation and socialization of manuals, process diagrams, CCP identification, as well as hygiene and signage materials. Post implementation, 62% overall compliance was achieved, highlighting an increase in good practices in each of the items evaluated, especially in personal manufacturing hygiene and raw materials. At the same time, statistical analysis of the physicochemical and microbiological variables showed that there was a significant difference (p < 0.05) between before and after implementation, which had a positive impact on the improvement of the company and compliance with the established indicators.